Analisis Pengaruh Keseimbangan Kehidupan Kerja Pada Karyawan Yang Sedang Mengambil Perkuliahan (Studi Kasus PT Kanmo Retailindo) : (Studi Kasus PT Kanmo Retailindo) - Moch Juhvahmi; Adrian Azhar Wijanarko (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the impact of work-life balance among employees of PT Kanmo Retailindo who are currently taking lectures. This research used a quantitative approach with data collection methods through questionnaires distributed to 130 respondents who are active employees and currently attending lectures. The variables in this study consist of time balance, involvement balance, satisfaction balance, and employee conditions. The sampling technique used purposive sampling with sample determination using the Slovin formula. The research data were analyzed using Statistical Product and Service Solution (SPSS). The results showed that most respondents were able to maintain a balance between work and lectures quite well. Respondents were also able to manage time, maintain involvement in work and academic activities, and have a fairly good level of satisfaction in carrying out their roles as employees and students. However, some respondents still experienced stress due to work and lecture demands carried out simultaneously. This study is expected to contribute to the development of human resource management science, especially those related to work-life balance among employees who carry dual roles as workers and students.